Mermaid Queen : the spectacular true story of Annette Kellerman, who swam her way to fame, fortune, & swimsuit history! - Corey, Shana (Scholastic Press, 2009)
As a child growing up in Australia, Annette Kellerman was a frail ugly duckling who dreamed of becoming a graceful ballerina. With courage and determination, she confronted a crippling illness to become an internationally known record-setting athlete who revolutionized the sport of swimming for women, a movie star who invented water ballet, and a fashion revolutionary who modernized the swimsuit.